Nilai-Nilai Pendidikan Moderasi Beragama dalam Kesenian Macopat di Kabupaten Sumenep : The Values of Religious Moderation Education in Macopat Art in Sumenep Regency - Fathorrahman, Fathorrahman; Ruqoiyah, Siti (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
The macopat art in Sumenep Regency, particularly in Aengdake Bluto Village, is a traditional cultural form with moral and religious educational values. Macopat serves as a medium for spreading values and education, instilling noble values within the community, especially in Java and Madura. However, in the current era of globalization, macopat art is rarely found and is at risk of disappearing. This study examines the issues surrounding the religious moderation values in macopat art in Aengdake Bluto Village, Sumenep. The research focuses on the implementation of macopat art and the religious moderation values embedded in it. This study employs a descriptive qualitative approach with a phenomenological method, involving interviews, observations, and documentation. The research subjects consist of macopat artists, local community members, and community leaders. The results indicate that the religious moderation values in macopat art include simplicity, tolerance, anti-violence, and accommodation toward local culture.